Metabolite profiling of chickpea (Cicer arietinum) in response to necrotrophic fungus Ascochyta rabiei - Raman, Rosy; Morris, Stephen; Sharma, Niharika; Hobson, Kristy; Moore, Kevin (Frontiers in Plant Science, 2024)
Introduction Ascochyta blight (AB) caused by the necrotrophic fungus Ascochyta rabiei is one of the most significant diseases that limit the production of chickpea. Understanding the metabolic mechanisms underlying chickpea-A.rabiei interactions will provide important clues to develop novel approaches to manage this disease. Methods We performed metabolite profiling of the aerial tissue (leaf and stem) of two chickpea accessions comprising a moderately resistant breeding line (CICA1841) and a highly susceptible cultivar (Kyabra) in response to one of the highly aggressive Australian A. rabiei isolates TR9571 via non-targeted metabolomics analysis using liquid chromatography-mass spectrometry. Results The results revealed resistance and susceptibility-associated constitutive metabolites for example the moderately resistant breeding line had a higher mass abundance of ferulic acid while the levels of catechins, phthalic acid, and nicotinic acid were high in the susceptible cultivar. Further, the host-pathogen interaction resulted in the altered levels of various metabolites (induced and suppressed), especially in the susceptible cultivar revealing a possible reason for susceptibility against A.r abiei. Noticeably, the mass abundance of salicylic acid was induced in the aerial tissue of the susceptible cultivar after fungus colonization, while methyl jasmonate (MeJA) was suppressed, elucidating the key role of phytohormones in chickpea-A. rabiei interaction. Many differential metabolites in flavonoid biosynthesis, phenylalanine, Aminoacyl-tRNA biosynthesis, pentose and glucuronate interconversions, arginine biosynthesis, valine, leucine, and isoleucine biosynthesis, and alanine, aspartate, and glutamate metabolism pathways were up- and down-regulated showing the involvement of these metabolic pathways in chickpea-A. rabiei interaction. Discussion Taken together, this study highlights the chickpea − A. rabiei interaction at a metabolite level and shows how A. rabiei differentially alters the metabolite profile of moderately resistant and susceptible chickpea accessions and is probably exploiting the chickpea defense pathways in its favour.